Experimental Research of Wetting and Drop Evaporation Processes on a Heated Substrate as a Method for Research Skills Development for Heat and Power Engineering Students; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Feoktistov D. V. Dmitriy Vladimirovich; Sharapova I. V. Irina Vyacheslavovna; Orlova E. G. Evgeniya Georgievna; Ponomarev K. O. Konstantin Olegovich (2015, 2015)
Title screen